C‐terminal–mediated homodimerization of Expanded is critical for its ability to promote Hippo signalling in Drosophila. Issue 13 (17th March 2022) - Wang, Guiping; Zhai, Chaojun; Ji, Xiaohui; Wang, Enlin; Zhao, Shanshan; Qian, Chenxi; Yu, Dongyue; Wang, Yunfeng; Wu, Shian
Abstract : Hippo signalling plays key role in tissue growth and homeostasis, and its dysregulation is implicated in various human diseases. Expanded (Ex) is an important upstream activator of Hippo signalling; however, how Ex activates Hippo signalling is still poorly understood. Here, we demonstrate that Ex forms a homodimer via C‐terminal interaction, and that the ExC2 region (912–1164 aa) is sufficient and essential for Ex dimerization. Functional analysis shows that ExC2 is required for Ex to promote the phosphorylation and inactivation of Yki in Drosophila cells. Further in vivo analysis shows that ExC2 is important for Ex to control Drosophila tissue growth. Our study, thus, uncovers a novel mechanism whereby Ex homodimerization mediates its full activation to promote Hippo signalling in growth control. Abstract : This study uncovers a novel mechanism whereby the Hippo pathway is regulated by homodimerization of Expanded (Ex). Mechanistically, Ex dimerization is mediated by its C‐terminal ExC2 domain. Ex∆C2 disrupts Ex homodimerization and thus decreases its inhibitory effect on Yki activity. More importantly, the ExC2 domain is demonstrated to be a specific regulatory element for wing growth control by genetic rescue assays.